Therapeutic angiogenesis by stem cell: new hope for the ischemic limbs (Community Based Medical Journal, 2019)
Critical limb ischemia in an intractable condition associated with high level of amputation, leading to low quality of life increase morbidity and mortality. It is often not treated by standard therapeutic modalities. Neoangiogenesis has been proposed as a novel method of treatment of such patients. Vascular Endothelial Growth Factor (VEGF) and Cytokine Fibroblast growth Factor (FGF1) have been shown to elicit neoangiogesis. Stem cells are progenitor cells which can differentiate in vivo into different type of cells. Collateral vessel formation after stem cell therapy. A case of 50 years old male, diabetic, hypertensive with dry gangrene of tip of left ring finger was treated with stem cell therapy after proper counseling. He received the therapy in the form of SVF (Stromal Vascular Fraction) from adipose tissue by local injection in the territory of the affected vessels. Following monitoring parameters were reported, improved wound status, local temperature change, oxygen saturation change in the ischemic zone. Outcome of stem cell therapy in this case including the rest pain disappeared at 14 days and the finger becomes warmed by 5°C in 3 weeks. The gangrenous area healed in 3 months. Amputation was averted. Angiogenesis is a complex process leading to new blood vessels formation. Mesenchymal stem cells (MSCs) are a type of adult stem cell which has an immunomodulatory effect. Stem cell therapy has been used to improve limb Vascularity. Stem Cells are likely to be an important modality to treat critical limb ischemia.CBMJ 2019 July: Vol. 08 No. 02 P: 40-46